Pensions in Costa Rica: Myths, Truths and Questions - Badilla Solano, Andrey (2018)
In this paper the reader will find a discussion on the impacts of the changes in the demographic profile of the country, the structural problem of employment during the Neoliberal Historical Project, the fiscal problem of the country and the insufficient tax base, the management of the administration and the mechanisms of internal control over the Pension Insurance of the Costa Rican Social Security Fund from a critical perspective.